2D phase-sensitive inversion recovery imaging to measure in vivo spinal cord gray and white matter areas in clinically feasible acquisition times - Papinutto, Nico; Schlaeger, Regina; Panara, Valentina; Caverzasi, Eduardo; Ahn, Sinyeob; Johnson, Kevin J.; Zhu, Alyssa H.; Stern, William A.; Laub, Gerhard; Hauser, Stephen L.; Henry, Roland G. (Journal of magnetic resonance imaging, 2015)
Purpose To present and assess a procedure for measurement of spinal cord total cross‐sectional areas (TCA) and gray matter (GM) areas based on phase‐sensitive inversion recovery imaging (PSIR). In vivo assessment of spinal cord GM and white matter (WM) could become pivotal to study various neurological diseases, but it is challenging because of insufficient GM/WM contrast provided by conventional magnetic resonance imaging (MRI). Materials and Methods We acquired 2D PSIR images at 3T at each disc level of the spinal axis in 10 healthy subjects and measured TCA, cord diameters, WM and GM areas, and GM area/TCA ratios. Second, we investigated 32 healthy subjects at four selected levels (C2‐C3, C3‐C4, T8‐T9, T9‐T10, total acquisition time <8 min) and generated normative reference values of TCA and GM areas. We assessed test–retest, intra‐ and interoperator reliability of the acquisition strategy, and measurement steps. Results The measurement procedure based on 2D PSIR imaging allowed TCA and GM area assessments along the entire spinal cord axis. The tests we performed revealed high test–retest/intraoperator reliability (mean coefficient of variation [COV] at C2‐C3: TCA = 0.41%, GM area = 2.75%) and interoperator reliability of the measurements (mean COV on the 4 levels: TCA = 0.44%, GM area = 4.20%; mean intraclass correlation coefficient: TCA = 0.998, GM area = 0.906). Conclusion 2D PSIR allows reliable in vivo assessment of spinal cord TCA, GM, and WM areas in clinically feasible acquisition times. The area measurements presented here are in agreement with previous MRI and postmortem studies. J. Magn. Reson. Imaging 2015;42:698–708.